Moradia: a pasárgada dos velhos? - Rosa, Maria Aparecida de Souza (2011)
This study has a qualitative approach, in which we adopted the method of action research, developed in the city of Sao Bernardo do Campo, and aimed to understand how the state, family and society take a position on the autonomy of the elderly live, the main factors influencing this choice, besides contributing to the exercise of citizenship of older people and drawing up new proposals and policies to facilitate access to housing for the elderly. We chose to use as a methodological procedure through participant observation of meetings, collective and individual interviews with semistructured questions, with three seniors, when they still lived in the hostel, from the preparatory phase for the new home, the change itself dictates and living in shared house. These procedures enabled the researcher to understand that the point of view of residents - while having autonomy, community interaction and support of the association - the address age-BE now is a first step. Because they are still searching for his Pasárgada particular